Crowd-sourced data for geospatial sanitation planning in informal settlements. (2016) - Holderness, Tomas; Kennedy-Walker, Ruth; Alderson, David; Evans, Barbara
Crowd-sourced geospatial data from OpenStreetMap and the Map Kibera project were used to model and optimise a proposed road-based sanitation network for the settlement of Kibera in Nairobi, Kenya. A Boolean multicriteria suitability analysis was employed to identify areas of land for transfer station infrastructure construction. Selected locations were then used in a spatio-topological network model for a theoretical road-based faecal sludge management scheme to service 158 public toilets in Kibera using Vacutug technology. The network model was employed to further optimise the location of transfer stations based on minimising total sewage transport time across the network. In this manner the paper establishes the utility of maps generated by communities and citizens as providing vital on-the ground information for sanitation engineering planning. Such information is in lieu of traditional formal sources of geospatial data, which are often not available in informal settlements. The study demonstrates crowd-sourced maps, when combined with geographical information systems for analysis, present new opportunities for sanitation infrastructure provision planning in unplanned communities.